Thermoelectric properties of Mg3Sb2−xBix single crystals grown by Bridgman method. (27th May 2015) - Kim, Soo Hyun; Kim, Chung Man; Hong, Yang-Ki; Sim, Kyung Ik; Kim, Jae Hoon; Onimaru, Takahiro; Takabatake, Toshiro; Jung, Myung-Hwa
Abstract: We studied the low-temperature thermoelectric properties of single crystals of Mg3 Sb2− x Bi x (0 ≤ x ≤ 2) grown by the Bridgman method. The crystals are well aligned along the hexagonal c axis as documented in the huge anisotropy of the electrical resistivity; ρ //c / ρ ⊥c = 100 for x = 2. Upon increasing x, the semiconducting behaviour in ρ ( T ) changes to the metallic behaviour, and the Seebeck coefficient S ( T ) at room temperature decreases from 590 μ V K −1 for x = 0 to 67 μ V K −1 for x = 2. Although the thermal conductivity at 300 K is as low as 0.88 W mK −1 for x = 0.7, the large resistivity of 1 Ω cm leaves the figure of merit, ZT, at a low level of 5.8 × 10 −3 at 300 K.